Zerumbone‐induced reactive oxygen species‐mediated oxidative stress re‐sensitizes breast cancer cells to paclitaxel. (25th March 2022) - Li, Jutao; Wang, Lingying; Sun, Yuxin; Wang, Zhe; Qian, Ye; Duraisamy, Vidhya; Antary, Tawfiq M. Al
Abstract: Chemotherapy is an effective approach for cancer therapy when plant‐derived sensitizers are combined with chemotherapeutics. Zerumbone, a natural phytochemical, has been documented to have various pharmacological roles. Here, we evaluated the chemosensitization potential of zerumbone in a breast cancer cell line in vitro. Zerumbone‐induced cytotoxicity in MCF‐7 cells was assessed by 3‐[4, 5‐dimethylthiazole‐2‐yl]‐2, 5‐diphenyltetrazolium bromide (MTT)‐based metabolic analysis. Reactive oxygen species (ROS)‐mediated mitochondrial membrane alterations, DNA damage, and apoptotic morphological changes were measured by fluorescence microscopy methods. A biochemical assay was employed to analyze Thiobarbituric acid reactive substances (TBARS) and antioxidant levels. Apoptotic marker expression levels were investigated by immunoblotting. MTT assay revealed that zerumbone significantly enhanced paclitaxel (PTX)‐induced cell death in breast cancer cells in a concentration‐dependent manner. Furthermore, our study demonstrated that zerumbone (15 μM) significantly enhanced ROS when combined with PTX (1 μM) treatment. Additionally, we observed that zerumbone enhanced the impairment of mitochondrial membrane potential and oxidative DNA damage, thereby inducing apoptosis in combination with PTX. Western blot analysis indicated that zerumbone significantly upregulated BAX, caspase‐7, and caspase‐9 expression and decreased BCL‐2 expression, thereby inducing proapoptotic protein‐mediated cell death combined with PTX. The prooxidant properties of zerumbone potentially resensitize breast cancer cells to PTX by enhancing intracellular ROS‐mediated oxidative stress. Abstract :